AKUNTABILITAS ANGGARAN PEMILIHAN BUPATI DAN WAKIL BUPATI BOYOLALI TAHUN 2020 - Susanti, F. Yeni; Suwardi, Suwardi; Suryo, Herning (Master of Public Administration, Universitas Slamet Riyadi, 2024)
Local elections in Indonesia in 2020 will be held simultaneously for regions whose term of office for regional heads ends in 2021. The simultaneous local election system in 2020 will be the fourth time has been held in Indonesia. The voting is planned to be held simultaneously in December 2020. The total number of regions that will carry out simultaneous local elections in 2020 is 270 regions with details of 9 provinces, 224 regencies and 37 cities. The 2020 Boyolali Regent and Deputy Regent elections are part of the 2020 Simultaneous Elections. This research aims to determine the accountability of budgeting and the 2020 Simultaneous Elections with case studies at the Boyolali General Election Commision, starting from budget planning, implementation, and reporting. The theory used is accounting theory according to Sujarweni (2015), accountability is a form of obligation for a person (leader/officer/executor) to guarantee that the duties and obligations they carry have been carried out in accordance with applicable regulations. The research method used is the Normative Legal Research Method, and the Observational Research Method Here a survey was carried out, by going directly to the research location to obtain primary data through interviews, and obtain budgeting data for the 2020 Boyolali Regent and Deputy Regent Elections. The results of the study show: first, the budgeting for the Boyolali Regent and Deputy Regent Elections in 2020 is running according to the corridor of government budgeting regulations. Second, in the implementation of programs and activities, there are changes between planning and budgeting, due to the dynamics of the implementation of the selection stages. However, these changes are carried out in accordance with the applicable laws and regulations. Third, in terms of reporting, there are findings from the examining institution that affect the quality of budget accountability for the 2020 election of the Boyolali Regent and Deputy Regent. In general, the conclusions that can be drawn from this research are that the budgeting for the 2020 Boyolali Regent and Deputy Regent Elections is quite accountable. Key word : accountability.